EARLY CHILDHOOD EDUCATION AND READING ABILITY - GAUR, JYOTI; SHARMA, SUNENA (THE PRIMARY TEACHER, 2012)
The ’normal’ ability at which a child might be expected to be able to read and comprehend written material is called reading ability. As in most areas of learning, people perform at different levels according to their skill, practice, motivation and so on. Reading is a cornerstone for a child’s success in school and indeed, throughout life. Without the ability to read well, opportunities for personal fulfilment and job success inevitably are lost. Early childhood education prepares the children for school skills. If the children do not receive ECE, their chances of coping with the further and formal education diminish. Keeping this hypothesis in mind that ECE has influence on the reading ability of children, the study aims to observe the difference between the reading ability of the children who received ECE as compared to those who did not